A combined day-ahead and intraday optimal scheduling strategy considering a joint frequency regulation reserve scheme among wind, photovoltaic, and thermal power - Zhu, Shulin; Wang, Haiyun; Wang, Weiqing; Chang, Xiqiang (Frontiers in Energy Research, 2023)
Under the premise of establishing a certain reserve power for frequency regulation, a new energy power plant (NEPP) transformed by frequency regulation control can participate in system frequency regulation. Considering the problem of cooperation between multiple NEPPs for reserve power for frequency regulation, this article presents a joint frequency regulation reserve scheme spanning wind, photovoltaic, and thermal power. A group of NEPPs composed of all NEPPs in the system works in the state of dynamic stepped output derating and participates in system frequency regulation together with thermal power units. Based on the joint frequency regulation reserve scheme and considering that the accuracy of new energy forecast directly affects the frequency regulation effect of NEPPs, we propose a combined day-ahead and intraday scheduling strategy considering the joint frequency regulation reserve scheme and derive the relevant scheduling model. The improved IEEE RTS 24-bus system is used as the test system for calculation. The results of the calculations show that the proposed strategy can optimize the participation scheme of frequency regulation of new energy, reduce the power and economic losses of new energy caused by participation in frequency regulation, and improve the ability of the power system to accommodate the output power of new energy under the premise of ensuring that the steady-state frequency deviation does not exceed the allowable frequency limits.